Annual evolution of the prescription of drugs with prognostic implications in acute decompensated heart failure with reduced ejection fraction - Raquel López-Vilella; Víctor DonosoTrenado; Borja Guerrero Cervera; Ignacio Sánchez-Lázaro; Luis Martínez Dolz; Luis Almenar Bonet (BMC Cardiovascular Disorders, 2024)
Abstract Background Quadruple therapy (renin angiotensin system inhibitors, beta-blockers, mineralocorticoid receptor antagonists and sodium/glucose cotransporter type 2 inhibitors [SGLT2i]) has become the current prognostic modifying treatment for heart failure (HF) with reduced ejection fraction (HFrEF). This study aimed to analyse the prescription´s evolution of this combination therapy, the analysis of each pharmacological group and the differences according to HF subgroups. Methods Retrospective analysis of consecutive patients admitted for cardiac decompensation. Inclusion period: from 1-1-2020 to 12-31-2022. Patients with left ventricular ejection fraction > 40% and deceased during admission were excluded. Finally, 602 patients were included. These were divided into: (a) de novo HF without previous heart disease (n:108), (b) de novo with previous heart disease (n:107), and (c) non-de novo (n:387). Results Over the study time, all pharmacological groups experienced an increase in drugs prescription (p < 0.001). The group with the largest prescription rate increase was SGLT2i (2020:20%, 2021:42.9%, 2022:70.4%; mean increase 47.2%). The discharge rate prescription of quadruple therapy increased progressively (2020:7.4%, 2021:21.1%, 2022:32.5%; mean increase 21.9%). The subgroup with the highest combined prescription in 2022 was de novo with previous heart disease (43.9%). Conclusion The pharmacological group with the largest prescription´s rate increase was SGLT2i. The percentage of patients discharged on quadruple therapy has progressed significantly in recent years, although it remains low. The most optimised subgroup at discharge was that of de novo HF with previous heart disease.